2010
DOI: 10.1212/wnl.0b013e318202038c
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 subtypes are associated with distinct atrophy patterns in frontotemporal dementia

Abstract: FTLD-TDP subtypes have distinct clinical and neuroimaging features, highlighting the relevance of FTLD-TDP subtyping to clinicopathologic correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
128
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 30 publications
16
128
0
Order By: Relevance
“…30 Consistent with our results, a recent study found mild to moderate p62 and TDP-43 staining in the thalamus of 4 C9ϩ carriers with MND. 31 Thalamic atrophy has been described in FTLD-TDP type A, 5,32 but not in type B, which is typically associated with FTD-MND. Although most FTD-MND cases show FTLD-TDP type B histology, an unexpected feature of C9ORF72 pathology is the frequency of FTLD-TDP type A.…”
Section: Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Consistent with our results, a recent study found mild to moderate p62 and TDP-43 staining in the thalamus of 4 C9ϩ carriers with MND. 31 Thalamic atrophy has been described in FTLD-TDP type A, 5,32 but not in type B, which is typically associated with FTD-MND. Although most FTD-MND cases show FTLD-TDP type B histology, an unexpected feature of C9ORF72 pathology is the frequency of FTLD-TDP type A.…”
Section: Demographicsmentioning
confidence: 99%
“…3,4 Many patients with FTD and ALS exhibit autosomal dominant family histories (FTD 10% 5 ; ALS 5%-10% 6 ; FTD-motor neuron disease [MND] 37% 7 ) and a number of large familial cohorts have been linked to a chromosome 9p region. [7][8][9][10][11][12] Recently, a noncoding expanded hexanucleotide repeat in chromosome 9 open reading frame 72 (C9ORF72) was identified as the cause of chromosome 9p-associated FTD and ALS.…”
mentioning
confidence: 99%
“…Few studies, however, have investigated whether these morphological features characterize the spectrum of FTDs, and whether thalamic morphology could assist in delineating various subtypes of this entity. Rohrer et al (2010) investigated 18 FTD patients who had antemortem MRI and postmortem confirmation of the TDP-43 subtype of FTD (positive immunoreactive inclusions), and using voxel-based morphometry reported that thalamic atrophy was useful in distinguishing FTD TDP-43 type 3 relative to types 1 and 2. Sharon et al (2012) investigated patterns of brain atrophy in FTD patients who were carriers for chromosome open reading frame 72 (C9ORF72) expansions, and reported greater thalamic atrophy (left > right) in carriers vs non carriers of this expansion.…”
Section: Thalamic Morphology In Other Neurodegenerative Disordersmentioning
confidence: 99%
“…35,36 Temporoparietal atrophy with sparing of midbrain can also be seen with Alzheimer disease. However, Alzheimer disease is unlikely in agPPA because no subject showed positive PiB-PET.…”
mentioning
confidence: 99%